Assessment of implementation status of Cigarettes and Other Tobacco Products Act (COTPA) and its awareness among residents in a block of Haryana - Ramashankar Rath; Anand Krishnan; Baridalyne Nongkynrih; Puneet Misra (Wolters Kluwer Medknow Publications, 2018)
Background: Legislative route is one of the known method to control behaviour of population. Cigarette and Other Tobacco Products Act is one of the laws enacted to control the use of tobacco in India lunched in the year 2003. Objective: The objective of this study was to find compliance of COTPA among tobacco stores and to find the knowledge of people regarding COTPA. Methods: All selected communities were studied by community audit. All stores selling tobacco products were assessed for its compliance to COTPA. Thirty participants from selected communities with in the age range of 18- 65 years were selected and interviewed for knowledge regarding COTPA. Results: A total of 218 stores were found to be selling tobacco. None of the stores were fully compliant to all COTPA clauses. Stores in rural areas were found to be more non-complaint than urban areas. 41% of stores were selling tobacco to minors, 10% were within 100 yards of schools.8% of schools have tobacco advertisement on façade and 24% displayed tobacco products openly. Around half of the participants (n-552) had heard about COTPA whereas only 4% were aware of all 4 provisions of COTPA. Conclusion: Although more than a decade passed since the law was enacted poor compliance and knowledge was found among participants.